2015
DOI: 10.1007/s00784-015-1606-1
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal spectrum and lacunarity as measures of complexity of osseointegration

Abstract: Quantitative description of early stages of osseointegration on titanium implants with different treatments should help develop a better understanding of this phenomenon, in general, and provide basis for further systematic experimental studies. Clinical practice should benefit from such studies in the long term, by more ready access to implants of higher quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A combination of FD and lacunarity analyses has been shown to improve the recognition of textures in images from several databases . Indeed, lacunarity and FD have been used to assess the changes in the trabecular bone from dental radiographs to observe healing process following dental implant placement and the structural changes of trabecular bone in osteoporosis . We have added porosity to this synergistic group of parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A combination of FD and lacunarity analyses has been shown to improve the recognition of textures in images from several databases . Indeed, lacunarity and FD have been used to assess the changes in the trabecular bone from dental radiographs to observe healing process following dental implant placement and the structural changes of trabecular bone in osteoporosis . We have added porosity to this synergistic group of parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, importantly, they found no correlation between FD and surface roughness . More recently, de Souza Santos et al employed both FD and lacunarity to monitor change in the surface patterns of blasted and acid etched titanium dental implants after submersion in simulated body fluid (SBF). They concluded that acid treatment and SBF immersion created the most complex and lowest lacunarity surfaces of those studied .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FD serves as a potent image texture descriptor, quantifying object complexity, with elevated values signifying more complex structures [ 7 , 12 , 19 , 22 , 37 , 41 ]. However, given that distinct fractal objects may exhibit identical FDs, lacunarity is employed to augment FD, offering insights into image heterogeneity [ 8 , 15 , 38 ] by evaluating the spatial arrangement of voids, hence elucidating the pixel distribution and organization, essentially quantifying space occupancy [ 3 , 15 ]. Homogeneous objects display low lacunarity with consistent gap sizes, whereas heterogeneous entities demonstrate high lacunarity [ 43 ].…”
mentioning
confidence: 99%